Análise dos requisitos para a implantação das tecnologias avançadas de manufatura - Fardin, Everton Luis (2011)
In this Dissertation are identified and related requirements appointed by the literature as necessary for the processes of implementation of advanced manufacturing technologies (AMTs) in manufacturing companies. A set of 18 requirements were identified and evaluated with the users and suppliers of AMTs to verify how each requirement has influenced the recent processes of project and implementation of AMTs. The level of influence of each condition was evaluated on a Likert scale from 1 (unimportant in the process) and 5 (crucial in the process) and the requirements considered most important were listed on a proposed roadmap for the design and implementation of automation in companies. The safety requisite was elected as the most important by the companies and the requisite total integration of the system was considered the least important for the implementation of AMTs, despite being the most mentioned by the authors surveyed.